Crowdfunding model as a source of financing for entrepreneurship and innovation projects in higher-education entities - Perez Moreno, Julian Sebastian; Pulido Pérez, Juan Felipe; Palacios Osma, José Ignacio (Ingeniería Solidaria, 2023)
Introduction: This article is the product of research on reducing the number of intermediaries by making use of Crowdfunding as an alternative source of low-cost financing, developed at the Universidad Distrital Francisco José de Caldas, in 2023.Problem: Although the term Crowdfunding is not new in the financial field, it is not very well known by the community, which means that it has not been applied as a recurrent financing alternative for projects or businesses in Colombia.Objective: This article presents a collaborative financing model for higher education institutions in Colombia, mainly for research groups oriented to the generation of new knowledge or spin-offs, with the aim of providing alternatives to classical financing models.Methodology: A literature review was conducted using the PRISMA methodology to identify, evaluate, and synthesize the existing body of knowledge produced by researchers, academics, or professionals.Results: The scope of this literature review encompasses the different types of crowdfunding, including its evolution over time and its inclusion in various economic areas. Additionally, it helps to visualize the level of knowledge about this concept among different university groups.Conclusion: The literature review examines the state of crowdfunding in Latin America, highlighting the lack of research compared to other regions. The impact of crowdfunding in various sectors, including technology, finance, and legislation, is emphasized. Furthermore, the need for theoretical reflection on how crowdfunding affects projects in the Southern Cone region is noted. The objective is to increase understanding and knowledge of crowdfunding among Latin American entrepreneurs and young people.
Keywords: crowdfunding; collaborative financing; model; higher education